Ontario's infrastructure boom: a socioecological fix for air pollution, congestion, jobs, and profits - Nugent, James Patrick (Environment & Planning A, 2015)
Infrastructure projects provide a spatial fix by increasing the scale and rate of capital accumulation, and because infrastructure projects themselves absorb massive amounts of productive and finance capital. I seek to explain the timing, character, and consequences of a Can $85 billion infrastructure boom in Canada's largest province, Ontario, between 2003 until 2013. I focus on the expansion and privatization of environmentally oriented infrastructure in Ontario via three policies: the conversion of public coal power plants to private natural gas and nuclear facilities; the Green Energy Act (a renewable energy feed-in tariffs programme); and The Big Move (a Can $50 billion dollar rapid transit plan using a public–private partnership model). I employ a Polanyian– O'Connor approach to emphasize the role of labour, environmental groups, and other social movement groups in bringing these investments about. I argue that infrastructure investments are not only a spatial fix aimed at finding capital a safe long-term investment and addressing class struggles around job creation. In Ontario these infrastructure investments have also provided the state with a broader socioecological fix for the economic and political contradictions stemming from air pollution and congestion. Social movements have pressured the government to address what James O'Connor refers to as the underproduction of the conditions of production: that is, degraded human health and quality of life; a deteriorating environment; and inadequate public infrastructure. Throughout the paper I emphasize how the socioecological fix in Ontario is being accomplished by advancing the neoliberal governance of public infrastructure. I point to how these neoliberal socioecological fixes are simply displacing socioecological crises to new spatial and temporal scales.
Geography
Keywords: Canada; Ontario; Polanyian-O'Connor approach; air pollution; fictitious commodities; human ecology; infrastructure; infrastructure and the environment; neoliberal environmental fix; privatization; saving and investment; second contradiction of capitalism; social movements; socioecological fix; spatial fix

The political economy of orphanage tourism in Cambodia - Guiney, Tess; Mostafanezhad, Mary (Tourist Studies, 2015)
A recent Aljazeera report on ‘Cambodia’s Orphan Business’ explains ‘how “voluntourism” could be fuelling the exploitation of Cambodian children’. Anti-orphanage tourism movements have emerged to resist the growth of Cambodia’s contested orphanage tourism industry, which is blamed for widespread corruption and the exploitation of children for profit. Taking a Polanyian political economy approach, this article illustrates how the emergence of and response to the orphanage tourism industry represent, in Karl Polanyi’s words, a ‘double movement’ between the neoliberalization of orphanages and the corollary protective countermovement by anti-orphanage tourism campaigns that challenge the industry’s morality and legitimacy. It argues that while resistance to the commodification of orphanages under the newly neoliberalized Cambodian economy reflects Polanyi’s double movement thesis, the limits of this resistance are also indicative of how countermovements are challenged by the broader political economy in which they operate.
Geography
Keywords: Cambodia; double movement; hospitality; leisure; sport & tourism; orphanage tourism; tourism; tourist studies; volunteer tourism

Land as fictitious commodity: the continuing evolution of women's land rights in Uganda - Naybor, Deborah (Gender, Place & Culture: A Journal of Feminist Geography, 2015)
In sub-Saharan Africa, colonial influences have altered traditional practices as a way to manage that which Polanyi labeled as ‘fictitious commodities’ of land, labor, and money. Land has now become a highly marketable commodity and an intrinsic part of the global economy. Over the past century, Uganda's land rights have evolved from communal rights to that of male-dominated, individual ownership practices that have excluded women. Despite constitutional provisions, which confer title of both a deceased husband's property rights and equal rights to property within a marriage to a wife, postcolonial patriarchal tradition prevails. This article examines historical changes in land rights in Uganda and discusses the impact of shifts in land rights from communal ownership to individual tenure, altering power structures and attempting to create marketable land title. The Ugandan women's movement's opposition to policies and implementation of laws that exclude women has been unable to facilitate the required changes in unbiased access to land rights, despite apparent victories in revisions to the letter of the law. Situated within contemporary interpretations of tradition and pressures of market demand, this article shows that women's access to landownership and use are restricted by misinterpretation of traditional law and a lack of enforcement of contemporary legal rights. To illustrate the impact of a lack of access to land, this article examines an empirical case study of widowed subsistence farmers in southern Uganda. Women in Uganda continue to lose ground, quite literally, decreasing the possibility of gender equity in terms of land. (English)
Geography
Keywords: Uganda; derechos de las mujeres; free enterprise; gender; género; land; land tenure; legal status of widows; legal status of women; property rights; tierra; viuda; widow; women's rights; 乌干达; 土地; 女性权利; 寡妇; 性别

Les paiements pour services environnementaux de la Fondation Natura Bolivia entre logiques réciprocitaires, redistributives et marchandes, - Bétrisey, Florence; Mager, Christophe (Revue Française de Socio-Économie, 2015)
La diffusion internationale des paiements pour services environnementaux (PSE) a été interprétée en 2010 par le gouvernement bolivien d’Evo Morales comme une réponse strictement néolibérale à la nécessité d’assurer une gestion durable des ressources naturelles. Supposée amener à terme à l’éviction de toute régulation autre que marchande – qu’elle s’applique à la nature ou aux rapports entre personnes –, la mise en place de PSE n’a pas été encouragée par les autorités nationales boliviennes. Des projets de PSE ont toutefois été lancés, dont les Acuerdos Reciprocos por el Agua (ARA), issus d’un partenariat public-privé dans le département de Santa Cruz. En analysant leur conception et leur fonctionnement au prisme du référentiel polanyien, nous montrons que, contrairement aux craintes gouvernementales, ces PSE ne font pas abstraction des logiques organisationnelles réciprocitaires et redistributives, ajustant au contexte local un objet global., ENG: The international dissemination of payments for ecosystem services (PES) has been interpreted in 2010 by the Bolivian government of Evo Morales as a strictly neo-liberal response to the need to ensure a sustainable management of natural resources. Supposed to contribute to the crowding-out of any other regulation than market – applied to the nature or the relationship between people – the implementation of PES was not encouraged by the Bolivian national authorities. However some PES projects stemming from a public-private partnership have been initiated at local level, as the Acuerdos Reciprocos por el Agua (ARA), in the department of Santa Cruz. Analysing their design and operating through the Polanyian framework, we show that, contrary to the government fears, these PES do not ignore the reciprocal and redistributive organisational logics, adjusting a global object to the local context.
Geography
Keywords: Bolivia; Bolivie; Polanyi; hybridity; hybridité; logique marchande; market logic; paiements pour services environnementaux; payments for ecosystem services; reciprocity; redistribution; réciprocité; sustainable management

The New ‘Passive Revolution’ of the Green Economy and Growth Discourse: Maintaining the ‘Sustainable Development’ of Neoliberal Capitalism - Wanner, Thomas (New Political Economy, 2015)
This paper analyses the rapidly emerging discourse of a green economy based on green growth. It highlights inherent conflicts and contradictions of this discourse such as the myth of decoupling growth from the environment, pollution generations and resource consumption. Using key theoretical constructs of both Gramsci and Polanyi, the paper argues that the green economy/growth discourse can be seen as a Gramscian ‘passive revolution’ whereby the dominant sustainable development discourse, subsumed by capitalist hegemony, is protected in the context of global environmental, economic and development crises. The ‘neoliberalising of nature’, or in other words, the privatisation, marketisation and commodification of nature, akin to Polanyi's fictitious commodities, continues and intensifies with green economy/growth strategies. Greening the economy and associated strategies of green growth divert attention from the social and political dimensions of sustainability and issues of social and international justice. In this way, the inexorable march or ‘sustainable development’ of neoliberal capitalism is maintained. This paper goes on to argue that contesting the claims of green economy/growth discourse through political struggles by civil society against the neoliberalisation of nature is a sign of a slowly emerging counter-hegemonic ‘double movement’ which challenges capitalist hegemony and the commodification of society–nature relations.
Geography
Keywords: GRAMSCI; Antonio; 1891-1937; environmental economics; fictitious commodities; green economy; green growth; neoliberalising nature; neoliberalism; passive revolution; privatization; research; social justice - environmental aspects; sustainable development